Design Build VoIP Technology Implementation on Network Applications IP Phone via a Different Intranet Network. - Shandi Noris; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2008)
Computer network technology and the internet today has become one of the important needs in life activities. Every day continues to grow, the development of a busy discussed and discussed today is the technology that lead to Next Generation Network (NGN) which will most likely be the technology platform on Internet Protocol (IP), one of the technology into use is a softswitch or known by the name Voice over Internet Protocol (VoIP). VoIP Technology able to communicate using voice infrastructure like the Internet using regular phone at no cost to regular phone. In addition, VoIP technology uses voice compression technology to provide efficiency and utilization bandwitdth, so that data communication is not disrupted.